Beyond Diabetes: Does Obesity-Induced Oxidative Stress Drive the Aging Process? - Adam B. Salmon (MDPI AG, 2016)
Despite numerous correlative data, a causative role for oxidative stress in mammalian longevity has remained elusive. However, there is strong evidence that increased oxidative stress is associated with exacerbation of many diseases and pathologies that are also strongly related to advanced age. Obesity, or increased fat accumulation, is one of the most common chronic conditions worldwide and is associated with not only metabolic dysfunction but also increased levels of oxidative stress in vivo. Moreover, obesity is also associated with significantly increased risks of cardiovascular disease, neurological decline and cancer among many other diseases as well as a significantly increased risk of mortality. In this review, we investigate the possible interpretation that the increased incidence of these diseases in obesity may be due to chronic oxidative stress mediating segmental acceleration of the aging process. Understanding how obesity can alter cellular physiology beyond that directly related to metabolic function could open new therapeutic areas of approach to extend the period of healthy aging among people of all body composition.